八物湯이 腦血流力學 變化에 미치는 效果 - 박철훈(Park Cheol Hun); 배인태(Bae In Tae); 정현우(Jeong Hyun Woo) (동의생리병리학회지, 2004)
The studywas designed to investigate the effects of Palmul-Tang(PMT) on the change of cerebral hemodynamics [regional cerebral blood flow(rCBF), pial arterial diameter(PAD) and mean arterial blood pressure(MABP)] in normal and cerebral ischemic rats. The change of rCBF and MABP were determinated by laser-doppler flowmetry(LDF), and the change of PAD was determinated by video-microscopy. The results in normal rats were as follows ; PMT significantly increased rCBF and PAD in a dose-dependent, and PMT increased MABP in a dose-dependent. This results were suggested that PMT significantly increased rCBF by dilating PAD. The results in cerebral ischemic rats were as follows ; Both rCBF and PAD were significantly and stably increased by PMT(10 ㎎/㎏, i.p.) during the period of cerebral reperfusion, which contrasted with the findings of rapid and marked increase in control group. The present authors thought that PMT had an anti-ischemic effect through the improvement of cerebral hemodynamics. KCI Citation Count: 3